BABYFYING MUSEUM TEXTS FOR YOUNGER VISITORS THROUGH AUGMENTED REALITY - Suryaputera, Achmad Nabil; Pradani, Eka Septi; Handayani, Suci Mia; Latief, Ahmad Danial; Ferdiansyah, Adi; Nabiha, Nisrina; Sanjaya, SF Lukfianka (Leksema: Jurnal Bahasa dan Sastra, 2024)
Museums have long been recognized as a place to study historical objects. However, at the same time, museums are considered unfamiliar to younger visitors due to the complexity of the descriptions of their artifacts. In order to overcome this problem, this research attempted to simplify the museum texts through an application named babyfication. The process of simplification involves three main components: conceptual simplification, modification for simplicity, and summarization of text. For enhancing the comprehension of the museum texts, augmented reality (AR) technology features are utilized in the process. Through a combination of simplified language, vibrant visuals, and interactive elements, this research tried to prove the beneficial outcomes from AR technology in bridging the gap between traditional museum texts and the developmental needs of young children, particularly dealing with their engagement with cultural artifacts. A qualitative research approach and Spradley’s data analysis technique were employed to figure out how the descriptive texts of museum artifacts are babyfied. Applying the theory of babyfication from Purnomo et al. (2021) as a ludic adaptation concept, it was revealed that textual, visual, and operative elements, that have been babyfied by using AR technology as a medium, tend to be textually simpler, more visually appealing, and make it easier for children to understand the information.